Octreotide acetate enhanced radio sensitivity and induced apoptosis in MCF7 breast cancer cell line - Salih Mahmoud, Alkhansa; Abu Bakar @ Zakaria, Md Zuki; Hamzah, Hazilawati; Tengku Ahmad, Tengku Ahbrizal Farizal; Mohd Noor, Mohd Hezmee (Elsevier, 2021)
Introduction: Breast cancer is the most common type of cancer among women. Radiotherapy is one of the treatment options for breast cancer; it plays a significant role in tumour control after surgery. However, radio resistance developed by tumour cells is the main problem in radiotherapy. As such, radiosensitization agents are used to improve radiotherapy efficiency. This study aims to investigate the role of octreotide acetate as a radiosensitizer for MCF7 cells. Methods: The treatments were designated into four groups: untreated cells, cells treated with octreotide acetate, cells treated with X-ray and cells treated with octreotide acetate in combination with X-ray irradiation. Cell viability assay, clonogenic assay, and qPCR was used as BAX apoptosis indicator marker analysis Morphological changes were examined under an inverted microscope. Results: The results showed more effectiveness for the octreotide acetate combination to X-ray radiation in the MCF7 cell line. Conclusion: These findings suggested that octreotide acetate enhanced radiosensitivity and induced apoptosis in MCF7 cell line.